The Influence of Human Resource Quality and Motivation on Work Productivity at Daycare Al Muhajirin Rewwin - Dinda Fransisca Wati; Rahmat Hidayat (Transpublika Publisher, 2024)
This study aims to analyze the influence of human resource (HR) quality and motivation on work productivity at Al Muhajirin Rewwin Daycare. The research adopts a quantitative approach with a survey design. Data were collected using a Likert-scale-based questionnaire completed by 50 parents of daycare children as respondents. The data were analyzed using Structural Equation Modeling Partial Least Squares (SEM PLS). The findings reveal that HR quality, measured through indicators of competence and expertise, and motivation, assessed through indicators of dedication, enthusiasm, and professionalism, significantly affect work productivity, measured by indicators of efficiency, effectiveness, and work outcomes. These results emphasize the importance of HR quality and motivation in creating a productive work environment in the early childhood education service sector. This study provides theoretical contributions to understanding the relationship between HR quality, motivation, and work productivity, particularly in the daycare context. Additionally, it offers practical recommendations for daycare managers to enhance HR quality and motivation through training programs, competency development, and fostering a work culture that promotes professionalism. The implications of this research are not only relevant to Al Muhajirin Daycare but also serve as a reference for other daycare operators aiming to improve work productivity through more effective and strategic HR management.